Potential of Jatropha Multifida L.- Placenta - Carboxymehyl Chitosan (CMC) Formulation as Regenerative Therapy for Burn Wounds - Mellyna Mellyna; Juniarti Juniarti; Nunung Ainur Rahmah (Eduvest - Journal of Universal Studies, 2026)
Second-degree burns are tissue injuries that often cause complications and require a long healing time. Previous studies have reported that natural ingredients such as Jatropha multifida L., placenta extract, and Carboxymethyl Chitosan (JM-P-CMC) have the potential to accelerate tissue regeneration, but no combined studies have been conducted on the three. The study aimed to evaluate the effect of the Jatropha multifida L.-Plasenta-CMC combination formulation on the number of fibroblasts as an indicator of tissue regeneration in second-degree burns. This experimental study used a post-test only control group design with 24 male Sprague dawley rats (200–250 g) induced burns on the back using a hot metal plate, then divided into four groups: control (Bioplacenton ® ), JM5%-P-CMC, JM10%-P-CMC, and JM15%-P-CMC. Topical treatment was carried out twice a day for 14 days. Data collection was carried out on days 5, 9, and 14, followed by histological analysis of skin tissue with Hematoxylin Eosin staining to count the number of fibroblasts. The results of the Kruskal-Wallis and Mann-Whitney tests showed a significant increase in the number of fibroblasts in all treatment groups compared to the control, with the highest results in the JM15%-P-CMC group. This study concluded that the combination was effective in enhancing tissue regeneration and has the potential to be developed as an innovative topical therapy based on natural ingredients.